Pharmacokinetics of doxorubicin following concomitant intravenous administration of olaratumab (IMC‐3G3) to patients with advanced soft tissue sarcoma. (10th December 2019) - Villalobos, Victor M.; Mo, Gary; Agulnik, Mark; Pollack, Seth M.; Rushing, Daniel A.; Singh, Arun; Van Tine, Brian A.; McNaughton, Rhian; Decker, Rodney L.; Zhang, Wei; Shahir, Ashwin; Cronier, Damien M.
Abstract: Background: Olaratumab, a fully human monoclonal antibody, selectively binds to human platelet‐derived growth factor receptor alpha and blocks ligand binding. This study assessed the effect of olaratumab on the pharmacokinetics (PK) of doxorubicin and the safety of olaratumab alone and in combination with doxorubicin. Methods: This open‐label randomized phase 1 trial enrolled 49 patients ages 27 to 83 with metastatic or locally advanced soft tissue sarcoma (STS). Patients participated in 21‐day treatment cycles (up to 8) until they met discontinuation criteria. In cycles 1 and 2, patients received olaratumab (15 mg/kg in Part A, 20 mg/kg in Part B) and doxorubicin (75 mg/m 2 ). In cycles 3 through 8, patients continued combination treatment (15 mg/kg olaratumab + doxorubicin). Effect of olaratumab on PK of doxorubicin was determined in patients who received all doses in cycles 1 and 2. Results: PK properties of doxorubicin administered alone or in combination with olaratumab (15 or 20 mg/kg) were similar for AUC(0‐ t last ), AUC(0‐∞), and C max . PK properties of olaratumab (15 or 20 mg/kg) were also similar when administered alone or in combination with doxorubicin. Three patients died (2 of disease progression and 1 of neutropenic enterocolitis). Fatigue and nausea (>75% of patients) were the most common treatment‐emergent adverse events (TEAEs). Other common TEAEs included musculoskeletal pain, mucositis, constipation, and diarrhea. Conclusions: Olaratumab at 15 or 20 mg/kg before doxorubicin infusion had no clinically relevant effect on systemic exposure to doxorubicin compared with doxorubicin alone in patients with metastatic or locally advanced STS. Abstract : In a phase 1 drug interaction study, the effect of olaratumab on the pharmacokinetics of doxorubicin was determined in patients with advanced soft tissue sarcoma. The pharmacokinetic properties of olaratumab alone or in combination with doxorubicin were similar.